2018
DOI: 10.3390/app8081366
|View full text |Cite
|
Sign up to set email alerts
|

Increased Internal Porosity and Surface Area of Hydroxyapatite Accelerates Healing and Compensates for Low Bone Marrow Mesenchymal Stem Cell Concentrations in Critically-Sized Bone Defects

Abstract: Featured Application: Volume and rate of tissue regeneration may be enhanced with increased scaffold porosity as well as increased numbers of non-cultured bone marrow cells. Abstract:For clinical treatment of skeletal defects, osteoinductive scaffolds must have the ability to conform to the unique geometry of the injury site without sacrificing biologically favorable properties, including porosity. This investigation seeks to combine the osteoinductive properties of porous hydroxyapatite (HA) scaffolds with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…The percentage of otolith grinding retention in the sieve was 0.4%, with 99.6% of particles with a particle size ≤ 45 μm, which is consistent with a very homogeneous granulometric behavior. It is likely that the large surface area of the otolith microparticles could promote fast dissolution due to the greater surface area exposed to the biological environment, allowing the chemical interaction between the biomaterial and the new formed bone, and accelerate the formation and the growth of the biologically active apatite layer [14]. Furthermore, recent reports have suggested that larger sized hydroxyapatite particles (20-100 μm) generate a less prolonged inflammatory response compared with smaller ones, which suggest that incorporation of larger sized particles into biomaterials scaffolds might prove beneficial in promoting a tissue regenerative microenvironment upon implantation [15].…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of otolith grinding retention in the sieve was 0.4%, with 99.6% of particles with a particle size ≤ 45 μm, which is consistent with a very homogeneous granulometric behavior. It is likely that the large surface area of the otolith microparticles could promote fast dissolution due to the greater surface area exposed to the biological environment, allowing the chemical interaction between the biomaterial and the new formed bone, and accelerate the formation and the growth of the biologically active apatite layer [14]. Furthermore, recent reports have suggested that larger sized hydroxyapatite particles (20-100 μm) generate a less prolonged inflammatory response compared with smaller ones, which suggest that incorporation of larger sized particles into biomaterials scaffolds might prove beneficial in promoting a tissue regenerative microenvironment upon implantation [15].…”
Section: Resultsmentioning
confidence: 99%
“…35,36 Therefore, many efforts have been made to minimize the amorphous content and increase the crystallinity ratio especially for HA coating of implant materials which is reported to improve the integration and survivorship of biomaterials within a living system. For example, nHA with high crystallinity has been reported to exhibit a lower degradation rate, a higher shear strength, a more stable bone integration, and to accelerate bone healing in critical size defects.…”
Section: Modification Of Milling Parameters and Their Importancementioning
confidence: 99%
“…For example, nHA with high crystallinity has been reported to exhibit a lower degradation rate, a higher shear strength, a more stable bone integration, and to accelerate bone healing in critical size defects. 35,36 Therefore, many efforts have been made to minimize the amorphous content and increase the crystallinity ratio especially for HA coating of implant materials which is reported to improve the integration and survivorship of biomaterials within a living system. 35,37 For this purpose, milling time was one of the selected processing variables in this study to modify the crystallinity ratio.…”
Section: Modification Of Milling Parameters and Their Importancementioning
confidence: 99%
“…For treatment of skeletal defects, osteo-conductive materials are critical to promote bone healing [34]. To determine whether PPy is a suitable substrate for cell culture in vitro, hDPSCs were seeded on PPy films.…”
Section: Osteogenic Potential Of Human Dental Pulp Stem Cells On Condmentioning
confidence: 99%